(untitled) (Iranian Journal of Kidney Diseases, 2020)
During the COVID-19 pandemic, we had a 25 years old male case without any underlying disease or history of autoimmune disease in COVID-19 Clinic, Isfahan, Iran. He presented with arthralgia and weakness so we started COVID-19 therapeutic regimen. In his hospitalization, creatinine increases and abnormalities in random urine sediment was seen. Methylprednisolone and cyclophosphamide were prescribed due to suspected glomerulonephritis. After renal biopsy the diagnose was confirmed as crescentic proliferative glomerulonephritis. The patient also, underwent plasmapheresis and intravenous immunoglobulin injection. He was discharged healthy without development of new pulmonary symptoms despite immunosuppressive treatment.